A Multiple Correspondence Analysis Study on Career Orientations of Aviation Management Students - Yavuz, Yade; Yaşar, Mehmet; Yorgancı, Mert; Dörtyol, Muhterem (Journal of Aviation Research, Maltepe University, 2025)
This study aims to understand the motivations of Aviation Management students in Turkey and their career trends after graduation. The study examines how the growth of the aviation industry and the demand for qualified labor force in this field affect students’ major preferences and career planning. In the study, data were collected through a questionnaire developed for Aviation Management students and the data obtained were evaluated using Multiple Correspondence Analysis (MCA). This method offers the opportunity to analyze the relationships between categorical variables in depth. The findings will reveal the basic dynamics behind the demographic, socio-economic and individual factors affecting students’ major preferences, as well as their sectoral tendencies. The results of the research are expected to contribute to the development of educational policies for the aviation sector and to the achievement of students’ career goals.